The Role of Water in Fast Plant Movements. (5th June 2019) - Edwards, J; Laskowski, M; Baskin, T I; Mitchell, N; DeMeo, B
Abstract: Plants moved onto land ∼450 million years ago and faced their biggest challenge: living in a dry environment. Over the millennia plants have become masters of regulating water flow and the toolkit they have developed has been co-opted to effect rapid movements. Since plants are rooted, these fast movements are used to disperse reproductive propagules including spores, pollen, and seeds. We compare five plants to demonstrate three ways, used alone or in combination, that water powers rapid movements: the direct capture of the kinetic energy of a falling raindrop propels gemmae from the splash cups of the liverwort, Marchantia ; the loss of water powers the explosive dispersal of the spores of Sphagnum moss; the alternate loss and gain of water in the bilayer of the elaters of Equisetum drive the walk, jump, and glide of spores; the gain of water in the inner layer of the arils of Oxalis drive the eversion of the aril that jettisons seeds from the capsule; and the buildup of turgor pressure in the petals and stamens of bunchberry dogwood ( Cornus canadensis ) explosively propels pollen. Each method is accompanied by morphological features, which facilitate water movement as a power source. The urn shaped splash cups of Marchantia allow dispersal of gemmae by multiple splashes. The air gun design of Sphagnum capsules results in a symmetrical impulse creating a vortex ring of spores. The elaters of Equisetum can unfurl while they are dropping from the plant, so that they capture updrafts and glide to new sites. The arils of Oxalis are designed like miniature toy "poppers." Finally, in bunchberry, the softening of stamen filament tissue where it attaches to the anther allows them to function as miniature hinged catapults or trebuchets.